ABPBI-based hollow fiber membranes for forward osmosis (FO) possessing low reverse salt flux - Thorat, Nitin M.; Lele, Ashish K.; Kharul, Ulhas K. (Desalination and Water Treatment, 2024)
The poly(2,5-Benzimidazole), known for its excellent thermochemical stability, was evaluated as a membrane material for forward osmosis. The dope in methane sulfonic acid was used to make hollow fiber membranes. The availability of bound MSA in HFMs was compared with its neutral form. Aqueous solutions of two common salts reported for FO (NaCl and MgCl2) were used as a draw solution at varying concentrations. The performance was determined in terms of water flux and reverse salt flux. The long-term performance of the membrane was assessed. The heat pretreatment of membranes was beneficial in offering low reverse salt flux, a crucial parameter in FO. The heat treatment at 350 degrees C exhibited excellent performance of low-RSF, irrespective of the draw solute used. The presence of MSA in the membrane matrix was found to be beneficial. Present HFMs exhibited reverse salt flux as low as 0.003 mol m-2 h-1 using 2 mol L-1 MgCl2 as a draw solution. The water flux of present membranes was lower than that of reported FO-membranes, which is attributable to the larger thickness of the present membranes. The findings will be used to make ABPBI-based membranes in thin form to elevate the fluxes and their practical applicability.
Keywords: ABPBI; Forward osmosis; Hollow fiber membrane; Low reverse salt flux

Scalable, interfacially synthesized, covalent-organic framework (COF)-based thin-film composite (TFC) hollow fiber membranes for organic solvent nanofiltration (OSN) - Kunjattu, Shebeeb H.; Thorat, Nitin M.; Gawas, Saroj; Kharul, Ulhas K. (ACS Applied Materials and Interfaces, 2024)
Covalent organic frameworks have great potential for energy-efficient molecular sieving-based separation. However, it remains challenging to implement COFs as an alternative membrane material due to the lack of a scalable and cost-effective fabrication mechanism. This work depicts a new method for fabricating a scalable in situ COF hollow fiber (HF) membrane by an interfacial polymerization (IP) approach at room temperature. The 2D COF film was constructed on a polyacrylonitrile HF substrate using aldehyde (1,3,5-trimethylphloroglucinol, Tp) and amine (4,4 `-azodianiline (Azo) and 4,4 `,4 `'-(1,3,5-triazine- 2,4,6-triyl) trianiline (Tta)) as precursors. The COF membrane on the PAN substrate showed 99% rejection of Direct red-80 with remarkable solvent permeance. The rejection analysis revealed that the structural aspects of the solute molecule play a major role in rejection rather than the molecular weight. We further optimized the precursor concentrations to improve the permeation performance of the resulting membrane. The durability study reveals excellent stability of the membrane toward organic solvents. This study also demonstrated the easy scalability of the membrane fabrication approach. The approach was further extrapolated to fabricate a cation-based COF membrane. These charged membranes exhibited an enhanced rejection performance. Finally, this approach can facilitate industrially challenging molecular sieving applications using COF-based membranes.
Keywords: covalent-organic framework; hollow fiber; interfacial polymerization; organic solvent nanofiltration; selective COF membrane

Poly(2,5-Benzimidazole)-based flat sheet membranes: investigating effects of dope solvent and membrane heat treatment on forward osmosis and acid enrichment performances - Somkuwar, Nitin C.; Thorat, Nitin M.; Ambade, Ashootosh; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2026)
The present work investigates two methods for preparing defect-free, symmetric membranes of the thermochemically robust polymer, poly(2,5-benzimidazole) (commonly known as ABPBI) for forward osmosis (FO), a growing technology for niche separations. The obtained polymer and membranes were analyzed for physical properties of significance. The FO analysis was performed using three salt solutions, viz., sodium chloride (NaCl), magnesium chloride (MgCl2), and sodium sulfate (Na2SO4). The effects of casting methodology (solvents present in the dope), membrane heat treatment, draw solution concentration, long-duration analysis, and FO-assisted enrichment of organic acids were evaluated. Some of the membranes exhibited extremely low reverse salt flux (RSF), which conveys the novelty of these membranes. Some of these membranes were analyzed using a high draw solution (DS) concentration (4 mol L-1) to enhance water flux and further employed to enrich organic acids. The aqueous acetic and methacrylic acid concentrations were enriched from 4.89 and 2.93 mol L-1 to 11.88 and 10.01 mol L-1, respectively. These results demonstrate an unmet need of concentrating methacrylic acid (a temperature-sensitive compound possessing a double bond). The present work demonstrates the potentials of ABPBI-based symmetric, thin membranes for FO and their industrial applicability for the first time.
Keywords: Applications; membranes; separation techniques